2012
DOI: 10.1159/000332822
|View full text |Cite
|
Sign up to set email alerts
|

Gonadotropin-Inhibitory Hormone Is a Hypothalamic Peptide That Provides a Molecular Switch between Reproduction and Feeding

Abstract: Objective: Gonadotropin-inhibitory hormone (GnIH)-3 is a neuropeptide that plays a major role in the regulation of reproduction and feeding in mammals. Materials and Methods: We measured endocrine and behavioural parameters of reproduction in sheep, and sexual behaviour in sheep, mice and cynomolgus monkeys. In addition, GnIH gene expression (in situ hybridization) was examined in ewes, and effects of GnIH-3 on food intake and energy expenditure were measured in various species. GnIH-3 was infused (i.v.) into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
133
3

Year Published

2013
2013
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 148 publications
(149 citation statements)
references
References 81 publications
13
133
3
Order By: Relevance
“…We provide in this study the first demonstration that RF9 has a strong food intake-suppressing effect in female rats with as low as 1 nmol. Our finding is indirectly in keeping with the data that GnIH-3 (RFRP-3) increases food intake in mammals without reducing energy expenditure (Clarke et al 2012). …”
Section: Central Administration Of P234 Inhibits Kisspeptininduced Fosupporting
confidence: 92%
See 1 more Smart Citation
“…We provide in this study the first demonstration that RF9 has a strong food intake-suppressing effect in female rats with as low as 1 nmol. Our finding is indirectly in keeping with the data that GnIH-3 (RFRP-3) increases food intake in mammals without reducing energy expenditure (Clarke et al 2012). …”
Section: Central Administration Of P234 Inhibits Kisspeptininduced Fosupporting
confidence: 92%
“…Therefore, the effect of kisspeptin on food intake seems to weaken in older age. In keeping with our finding, there was no effect of kisspeptin on food intake in sheep (Clarke et al 2012). While central kisspeptin administration has been initially reported not to have any significant effects on food intake and body weight in rats (Castellano et al 2005), central administration of kisspeptin has been recently shown to increase meal intervals, resulting in a decrease in nocturnal food intake in mice (Stengel et al 2011).…”
Section: Central Administration Of P234 Inhibits Kisspeptininduced Fosupporting
confidence: 89%
“…and it has been proposed that GnIH functions as a "molecular switch" between reproduction and 847 feeding in vertebrates [10] This review has looked back over a period of twenty-five years of research on 860…”
Section: Localisation Of Salmfamide-like Immunoreactivity In Brittle mentioning
confidence: 99%
“…Diverse data from a wide variety of vertebrate taxa indicate that these neuropeptides play a role in the regulation of reproduction in response to short-term (circadian) and long-term (seasonal) environmental changes , Clarke & Parkington 2014. Moreover, both neuropeptides act as conduits/mediators for transferring the impact of body internal cues such as gonadal steroids and current energy status to the reproductive axis (Smith et al 2007, Clarke et al 2012, Smith 2013.…”
Section: Introductionmentioning
confidence: 99%